Burden, Positive Aspects, and Predictive Variables of Caregiving: A Study of Caregivers of Patients with Pediatric Glaucoma - Yingting Zhu; Jinyun Gao; Xinyan Li; Qiongman Yang; Yu Lian; Huiming Xiao; Wenmin Huang (Journal of Ophthalmology)
Purpose. To determine the presence of burden and positive aspects among caregivers of patients with pediatric glaucoma (PG) and to establish whether they were influenced by the characteristics of the caregivers and the patients. Method. This study was designed to be cross-sectional and descriptive. The Chinese version of the Caregiver Burden Inventory (CBI) and the Positive Aspects of Caregiving (PAC) questionnaires were used to evaluate the caregivers. The demographic data of the enrolled participants were also collected. The CBI and the PAC scores were analyzed in relation to each other and different characteristics of the patients with PG and their caregivers through a generalized linear regression model. Result. Most of enrolled 57 caregivers were found to act with a moderate level of burden and benefits. The emotional subscale score of the CBI is negatively related to the aggregate score of the PAC and to that of outlook on life. Moreover, patients with a longer duration of disease and caregivers who were female, had jobs, had lower education levels, and had lower household incomes have qualities that are positively related to the summary score of the CBI. However, no factors we collected were significantly related to the PAC score. Conclusion. The results suggest that caregivers perceive positive and negative experiences in the care and support of patients suffering from PG. In addition, we should pay more attention to the caregivers with a high risk of experiencing caregiver burden, especially females with jobs and also with lower incomes and lower levels of education.